CRESCIMENTO INICIAL DE ANADENATHERA MACROCARPA (BENTH.) BRENAN EM RESPOSTA A ADIÇÃO DE BIOCARVÃO AO SUBSTRATO - FRANCO, Alex Quaresma; COUTO, Allan Motta; VIEIRA, Vanessa Aparecida Cassol; SILVA, Hebert Lizardo Germano; MENEZES, Rayane Aparecida Silva; CARVALHO, Henrique Silva (ANAIS DO ENIC, 2018)
-